2018
DOI: 10.1177/0256090918774697
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Customer Loyalty in Banking Sector: A Mediational Study

Abstract: Executive Summary The competition among the organizations is increasing continuously and there has been a rapid shift in the business process deliverance. Financial service firms are striving to improve their business processes by liaising with customers to survive and compete successfully. The literature has obstinately emphasized on the utmost importance of trust and loyalty to survive in the financial sector. This study aims to explore the role of customer knowledge management (CKM) and satisfaction as ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
1
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 73 publications
9
43
1
18
Order By: Relevance
“…Acceptable values of fit as reported by Schermelleh-Engel et al (2003) can be seen in Table 1. The results indicated that the current model fitted the data well, Chi2/df value was 2.331 which is less than 3 (Hoe 2008), GFI value was 0.951 which is close to the acceptable value of fit, CFI value was 0.958 which is higher than 0.95, RMSEA value was 0.061 which is greater than 0.05 and less than 0.10 (Hooper et al 2008, Bhat et al 2018. Finally, AGFI value was 0.862 which is higher than 0.80 (Stacciarini and Pace 2017) 3.…”
Section: Model Fitmentioning
confidence: 78%
“…Acceptable values of fit as reported by Schermelleh-Engel et al (2003) can be seen in Table 1. The results indicated that the current model fitted the data well, Chi2/df value was 2.331 which is less than 3 (Hoe 2008), GFI value was 0.951 which is close to the acceptable value of fit, CFI value was 0.958 which is higher than 0.95, RMSEA value was 0.061 which is greater than 0.05 and less than 0.10 (Hooper et al 2008, Bhat et al 2018. Finally, AGFI value was 0.862 which is higher than 0.80 (Stacciarini and Pace 2017) 3.…”
Section: Model Fitmentioning
confidence: 78%
“…The results of the analysis show that trust in the product has a positive and significant effect on the loyalty of the credit card users of Bank Rakyat Indonesia (BRI) in Padang Panjang city. Satisfaction has a positive impact on customer trust, and customer trust has a significant impact on loyalty (Bhat, 2018). In addition, trust mediates the effect of knowledge and satisfaction towards loyalty.…”
Section: Discussionmentioning
confidence: 97%
“…Companies need to be responsive and sensitive to customers' expectations to remain competitive. According to Bhat, Darzi, and Parrey (2018), the customer has become a key element for any firms' long-term growth, sales and marketing strategy, resource allocation, product development, and overall profitability" (92-93). An important element to successful strategy success is customer knowledge management (CKM) and customer satisfaction (Bhat et al, 2018, p.92).…”
Section: Dealing With Customer Relationshipsmentioning
confidence: 99%
“…According to Bhat et al (2018), customer loyalty is "a deeply held commitment to rebuy or re-patronize a preferred product/service consistently in the future, thereby causing repetitive same-brand or same-brand set purchasing, despite situational influences and marketing effort having the potential to cause switching behavior" (p.94). According to Elmontaser & Jaafar Alhabshi (2016), focus of marketers has slowly shifted "from concentrating on improving operational performance to raised order constructs, such as customer loyalty and customer retention which are considered to contribute to company's long-term achievement" (p.185).…”
Section: Dealing With Customer Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation